(untitled) (Scientific journal of the Fergana State University, 2026)
The article studies the theoretical and methodological foundations of developing logical thinking skills in future teachers, the methodology for developing logical thinking skills in future teachers based on philosophical education, and the effectiveness of developing logical thinking skills in future teachers. Also, methodological aspects of developing logical thinking skills in future teachers based on philosophical education are analyzed.